Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.neuron.2020.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Tau Reduction Prevents Key Features of Autism in Mouse Models

Abstract: Highlights d Tau reduction prevents autism-like behaviors in Scn1a RX/+ and Cntnap2 À/À mice d Tau reduction also prevents PI3K overactivation and megalencephaly in these models d Tau interacts with PTEN via its proline-rich domain and suppresses PTEN activity d PTEN is a critical mediator of the beneficial effects of tau reduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(117 citation statements)
references
References 89 publications
3
107
4
Order By: Relevance
“…In support of this notion, Tau has been shown to interact with other phosphatases, such as protein phosphatase 2A, through its proline-rich domain, which is also recognized by Fyn [51]. During the revision of our manuscript, a study has been published which shows that Tau indeed interacts with PTEN via Tau's proline-rich domain [57]. As diseaserelevant phosphorylation or FTLD mutations of Tau can increase the association with Fyn [3,31], these pathological changes may release PTEN from being restricted by Tau.…”
Section: Discussionmentioning
confidence: 58%
“…In support of this notion, Tau has been shown to interact with other phosphatases, such as protein phosphatase 2A, through its proline-rich domain, which is also recognized by Fyn [51]. During the revision of our manuscript, a study has been published which shows that Tau indeed interacts with PTEN via Tau's proline-rich domain [57]. As diseaserelevant phosphorylation or FTLD mutations of Tau can increase the association with Fyn [3,31], these pathological changes may release PTEN from being restricted by Tau.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, in a mouse line of Shank3B -/-(SH3 and multiple ankyrin repeat domains 3 deficiency, modeling the Phelan McDermid Syndrome), Tau reduction was not beneficial. The authors suggested that the PI3K/Akt/mTOR (protease inhibitor 13/ AKT Serine/Threonine kinase/mTOR) pathway, activated by interactions of Tau and PTEN (phosphatase and tensin homolog) plays a key role in the ASD development in the Scn1a RX/+ and the Cntnap2 -/cases, but not in the Shank3B -/mouse 37 . Notably, MTOR was found to be regulated by ADNP in human postmortem tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tau appears to be important for permitting seizure activity, and there is strong evidence that MAPT −/− mice [148], or mice treated with tau antisense oligonucleotides [59] are resistant to pentylenetetrazol-induced seizures. Crossing MAPT −/− mice with genetic models of epilepsy [105], AD [219] and ASD [249] can rescue hyperexcitability and spontaneous epileptiform activity. As such, a role for tau in promoting or regulating neuronal excitability seems likely.…”
Section: Regulating Neuronal Hyperexcitability: Could Tau and Aβ Act mentioning
confidence: 99%